Animation art : From pencil to pixel, the history of cartoon, anime & CGI - Ball, Ryan.; Beck, Jerry, ed. (London : Flame Tree Pub., 2004)
A comprehensive artbook covering the history of animationfocusing on the creative styles of Walt Disney and Warner Brothers.
Keywords: Animated films -- History; Computer animation -- History